Disseminated varicella zoster virus infection following live attenuated herpes zoster vaccine: descriptive analysis of reports to Australia's spontaneous vaccine pharmacovigilance system, 2016–2020. Issue 1 (27th January 2023) - Li-Kim-Moy, Jean; Phillips, Anastasia; Morgan, Adelaide; Glover, Catherine; Jayasinghe, Sanjay; Hull, Brynley P; Dey, Aditi; Beard, Frank H; Hickie, Megan; Macartney, Kristine
Abstract : Objectives: To examine the reported incidence and features of disseminated varicella zoster virus (VZV) infection following live attenuated herpes zoster vaccine live (ZVL: Zostavax, Merck) in immunocompromised people in Australia. Design and setting: ZVL was funded in 2016 in Australia for people aged 70 years, with a catch-up programme for those 71–79 years. From 2016 to 2020, three deaths due to disseminated vaccine-strain VZV infection occurred following inadvertent ZVL administration in individuals with varying levels of immunocompromise. This descriptive study examined 4 years of national surveillance data reported to the Therapeutic Goods Administration's Adverse Event Monitoring System (AEMS). Denominator data for rates were from doses recorded in the Australian Immunisation Register. Participants: Individuals vaccinated between 1 November 2016 and 31 December 2020 who experienced adverse event(s) following immunisation (AEFI) after ZVL recorded in the AEMS. Primary and secondary outcome measures: Rates and outcomes of confirmed (Oka strain positive) or probable disseminated VZV infection, and inadvertent administration of ZVL in immunocompromised individuals. Results: 854 AEFI were reported from 1 089 966 doses of ZVL administered (78.4 per 100 000 doses). Of those, 14 were classified as confirmed (n=6, 0.55 per 100 000) or probable (n=8) disseminated VZV infection. The confirmed cases were all hospitalised, and most (5/6) were immunocompromised; three cases died. Thirty-seven individuals were reported as vaccinated despite a contraindication due to immunocompromise (3.4 per 100 000), with 12/37 (32%) hospitalised. Conclusions: Disseminated VZV is potentially life-threatening and occurs mostly in those with severe immunocompromise. Inadvertent administration of ZVL to immunocompromised individuals has occurred despite initial provider guidance and education. Multiple additional strategies to assist providers to identify contraindications have been implemented to prevent adverse outcomes.